PENGARUH LITERASI KEUANGAN DAN LOCUS OF CONTROL TERHADAP PERILAKU MENABUNG RUMAH TANGGA DI KABUPATEN SUMBAWA - Nurasia Nurasia; Hartini Hartini (Politeknik Bisnis Indonesia, 2023)
This research aims to examine the influence of financial literacy and locus of control on household savings behavior in Sumbawa Regency. This research is quantitative research with an associative approach. The population used was all housewives in Sumbawa Regency with a sample of 259 respondents who were housewives with an age range of 18-70 years. Data collection techniques using questionnaires and data analysis tools using Stata. The results of this research show that financial literacy has a positive and significant influence on the saving behavior of housewives in Sumbawa Regency and locus of control has a positive and significant influence on the saving behavior of housewives in Sumbawa Regency.